ШАХСГА ЙЎНАЛТИРИЛГАН ЁНДАШУВ ЎҚУВЧИЛАРНИ ИЖОДИЙ ФАОЛЛИККА УНДАШ АСОСИ СИФАТИДА - Юсупова, Г.З. (SCIENCE and SOCIETY, 2018)
The article is about those sides of creative activities of primary classes‘ pupils which are connected with psychological and philosophical factors. There are also revealed the tasks done by learners in the teaching and educational activity and the content of educational process aimed to the development of the creative inclinations in pupils.
Keywords: creative activity; work ability; communication; teaching process; education content; personality; social activity; pupil key competencies; subject competencies